McGraw-Hill Multimedia encyclopedia of science & technology - McGraw-Hill Information Services Company (New York : McGraw-Hill, 1994)
Multimedia reference work which contains articles and illustrations from the McGraw-Hill encyclopedia of science & technology (7th ed., 1992) and scientific terms from the McGraw-Hill dictionary of scientific and technical terms (5th ed., 1994) with additional material created for this CD-ROM. Has animation to demonstrate difficult concepts, contains biographies, maps, sky maps, and study guides and is both a dictionary and encyclopedia.
In container (24 x 18 x 3 cm).
Title from disk surface.
System requirements: IBM PC or compatible with 386 processor; 4MB RAM; Microsoft Windows 3.1; hard drive with 3MB free space; VGA or SVGA color monitor; MPC-compatible sound board (optional); Microsoft or compatible mouse (optional); CD-ROM drive (ISO 9660).
Disk characteristics: CD-ROM.
Keywords: Science -- Encyclopedias; Technology -- Encyclopedias; Science -- Dictionaries